Stock Assessement of Sulphur Goatfish (Upeneus sulphureus Cuvier, 1829) in Sunda Strait, Banten : Pendugaan Stok Ikan Kuniran (Upeneus sulphureus, Cuvier 1829) di Perairan Selat Sunda, Banten - Hikmatul Azizah; Mennofatria Boer; Nurlisa A. Butet (Tropical Fisheries Management Journal, 2020)
Sulphur goatfish (Upeneus sulphureus) is one of a demersal fish as the main commodity in Sunda Strait. This research aimed to assess the stocks of sulfur goatfish (Upeneus sulphureus) in Sunda Strait, Banten as a basic management for optimum and sustainable used. Collecting samples were conducted with Stratified Random Sampling approach in May-October 2018 at PPP Labuan, Banten. The research showed the gender ratio of sulfur goatfish was 0.92:1. The growth pattern of the males fish was negative allometric and the female was isometric. Pukat cincin was the fishing gear become the standard for other fishing gears. Stock status of sulfur goatfish (Upeneus sulphureus) fisheries in Sunda Strait, Banten had indicated overfishing.